Fiqh hadith dalam koleksi hadis-hadis hukum oleh Hasbi Ash-Shiddieqy: Kajian terhadap topik-topik terpilih / Nurul Farhana Yusuf - Nurul Farhana , Yusuf (2019)
Nowadays the development in thinking has given the public an openness in evaluating something. In matters that relate to religion or syariah, it gives a positive effect but the opposite will happen if openness is arbitrarily used. In Indonesia, there are so many intellectuals, whereby Hasbi Ash-Shiddieqy is one of them. Hasbi is an Indonesian caliber scholar , especially in his ideas of thought and knowledge of Islamic law. He was the first person to publish a book on legal issues entirety, entitled “The Collection of Hadith Law”. The purpose of this study is to theoretically describe fiqh and hadith, as well as to review and evaluate the ijtihad (independent reasoning) by using Hasbi‟s methods in establishing the law in both fields (hadith dan jurisprudence). In addition, the researcher has also examined his contributions in those fields. The methodology used was focused on library research, with reference to Hasbi‟s works and other secondary sources thatrelated to him . This study found that in determining the law, Hasbi did not dissociate himself from the al-Quran and hadith referring to the views of Islamic scholars based on the hadith understanding, prioritizing the maslahah needs and considering the maqasid of syariah (objectives of syariah).